Orthodontic bracket bonding to glazed full-contour zirconia - Ji-Young Kwak; Hyo-Kyung Jung; Il-Kyung Choi; Tae-Yub Kwon (Restorative Dentistry & Endodontics, 2016)
Objectives This study evaluated the effects of different surface conditioning methods on the bond strength of orthodontic brackets to glazed full-zirconia surfaces.